Arctic Invasive Alien Species: Strategy and Action Plan 2017 - Conservation of Arctic Flora and Fauna (CAFF); Protection of the Arctic Marine Environment (PAME) (Conservation of Arctic Flora and Fauna and Protection of the Arctic Marine Environment, 2017)
Arctic biodiversity is an irreplaceable cultural, aesthetic, scientific, ecological, economic, and spiritual asset. The envisioned goal of the Arctic as ecologically, culturally, and economically sustainable necessitates a focus on the factors that threaten the region's environment and human health. Invasive alien species represent a significant and rapidly emerging threat to Arctic ecosystems and inhabitants who depend upon these ecosystems for their livelihoods and well-being. Globally, invasive alien species are among the most significant drivers of biodiversity loss (McNeely et al. 2001, Bellard et al. 2016) and, in some ecosystems, they are clearly the primary contributors to species endangerment and ecosystem degradation (esp. Islands, Reaser et al. 2007).